Legal Analysis of Issues Related to User-Generated Content in Derivative Works - Li, Junyi (International Journal of Social Sciences and Public Administration, 2024)
In the information age, the barriers to individual creative production have significantly lowered, leading to new developments in the arts, while also giving rise to various legal issues. One such challenge lies in defining originality and the boundaries of infringement in derivative works. This is especially problematic on user-generated content (UGC) platforms, where new forms of creative expression, such as video mashups, lack clear standards for determining infringement. By comparing international practices and considering the specific context of China, this paper seeks to balance the interests of creators, platforms, and original authors. The goal is to encourage creativity while respecting the copyright of original authors, ultimately achieving a win-win situation in the creative market and fostering cultural innovation and freedom of expression.